Analysis of Islamic Economic Law on the Elements of Tadlis and Gharar in the Practice of Rice Adulteration (A Case Study at Johar Rice Market Karawang) - Tristia Qurrotu Ain; Anggi Irawan; Rizki Dwi Anggraini (Universitas KH. Abdul Chalim Mojokerto, 2026)
The practice of rice adulteration is still found in trade to adjust quality and prices according to the needs of the community. This study aims to analyze the practice of rice adulteration at Johar Rice Market, Karawang, based on the concepts of Tadlis and Gharar as stipulated in the Compilation of Sharia Economic Law (KHES). This study employed a qualitative method with an empirical juridical approach through observation, interviews, and documentation. The results indicate that rice mixing is carried out to provide variations in quality and price; however, information regarding the quality of the rice is not always disclosed to buyers. Based on the analysis of KHES, this practice contains elements of deception as referred to in Article 33 and Article 34 of KHES, which constitute Tadlis in terms of quality, and also contains Gharar regarding the object of the transaction as referred to in Article 76 letter (f) of KHES, since buyers do not have definite knowledge of the quality of the rice at the time the contract is concluded. Therefore, the practice of rice mixing can only be justified if it is conducted honestly and transparently.